A colorimetric and fluorometric oligothiophene-indenedione-based sensor for rapid and highly sensitive detection of cyanide in real samples and bioimaging in living cells. (April 2019) - Guo, Zongrang; Hu, Tingting; Sun, Tao; Li, Tianduo; Chi, Hong; Niu, Qingfen
Abstract: A new simple oligothiophene-indenedione-based sensor3TI has been synthesized for the highly reactive and selective detection of cyanide anion (CN − ) in 70% aqueous media. The sensor3TI displays distinct colorimetric and fluorometric detection of CN − due to the addition of CN − to the electron-deficient indenedione-vinyl group of3TI, which hampers intramolecular charge transfer (ICT) efficiencies. The recognition mechanism of3TI for CN − was confirmed by the optical measurements, 1 H NMR titration, FTIR spectra, HRMS analysis, and TD-DFT calculations. The sensor3TI for CN − shows the outstanding advantages of high fluorescence brightness, fast response time (30 s), low detection limit (31.3 nM), minimal pH dependence in the physiologically relevant range, and excellent selectivity in presence of other competitive anions. Encouraged by these desirable sensing properties, the3TI has been successfully used for determination of CN − in real water and food samples, silica-based sensing kits and fluorescence imaging in living cells with satisfactory results. Graphical abstract: Highlights: A new oligothiophene-indenedione-based sensor3TI has been synthesized. Sensor3TI exhibits colorimetric and turn-on fluorescent response to CN − . Sensor3TI for CN − shows rapid response and high selectivity. 3TI was used to detect CN − in water, food, silica and living cells.